2023
DOI: 10.5435/jaaos-d-21-01194
|View full text |Cite
|
Sign up to set email alerts
|

Practical Application of the 2020 Distal Radius Fracture AAOS/ASSH Clinical Practice Guideline: A Clinical Case

Abstract: The Clinical Practice Guideline Management of Distal Radius Fractures released by the American Academy of Orthopaedic Surgeons and the American Society for Surgery of the Hand is a summary of the available evidence designed to guide surgeons and other qualified physicians in the management of distal radius fractures. According to this guideline, age of 65 is used as a proxy for functional activity and can serve as a threshold under which patients are likely to benefit from surgical fixation and over which pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…However, follow-up studies found no significant differences in pain or functional improvement between these approaches, sparking debate on the best strategy . British guidelines recommend closed reduction and cast immobilization as primary treatments . However, drawbacks of the conventional cast, such as bulkiness, have spurred treatment innovations .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, follow-up studies found no significant differences in pain or functional improvement between these approaches, sparking debate on the best strategy . British guidelines recommend closed reduction and cast immobilization as primary treatments . However, drawbacks of the conventional cast, such as bulkiness, have spurred treatment innovations .…”
Section: Introductionmentioning
confidence: 99%
“… 16 British guidelines recommend closed reduction and cast immobilization as primary treatments. 17 However, drawbacks of the conventional cast, such as bulkiness, have spurred treatment innovations. 18 , 19 , 20 , 21 The rise of 3-dimensional (3D) printing in orthopedics has led to bespoke splints with superior clinical efficacy, lightweight design, and better ventilation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent joint guidelines issued by the American Academy of Orthopedic Surgeons and American Society for Surgery of the Hand have suggested that both techniques are valid for fixation, but the question of best surgical technique still remains controversial. 21…”
mentioning
confidence: 99%
“…Recent joint guidelines issued by the American Academy of Orthopedic Surgeons and American Society for Surgery of the Hand have suggested that both techniques are valid for fixation, but the question of best surgical technique still remains controversial. 21 Therefore, we conducted a literature search to identify RCTs comparing K-wire and VLP techniques for unstable DRFs and performed a meta-analysis with the intent of evaluating and comparing the evidence in terms of clinical functional outcomes, radiographic outcomes, joint range of motion (ROM), and postoperative complications to determine the preferred technique in the operative management of unstable DRF.…”
mentioning
confidence: 99%